Usability Testing of the iPhone App to Improve Pain Assessment for Older Adults with Cognitive Impairment (Prehospital Setting): A Qualitative Study - Docking, Rachael E; Lane, Matthew; Schofield, Pat A (Pain medicine (Malden, Mass.), 2018)
Abstract Objectives Pain assessment in older adults with cognitive impairment is often challenging, and paramedics are not given sufficient tools/training to assess pain. The development of a mobile app may improve pain assessment and management in this vulnerable population. We conducted usability testing of a newly developed iPhone pain assessment application with potential users, in this case as a tool for clinical paramedic practice to improve pain assessment of older adults with cognitive impairment. Methods We conducted usability testing with paramedic students and a Delphi panel of qualified paramedics. Participants studied the app and paper-based algorithm from which the app was developed. The potential use for the app was discussed. Usability testing focus groups were recorded, transcribed verbatim, and analyzed using a thematic approach. Proposed recommendations were disseminated to the Delphi panel that reviewed and confirmed them. Results Twenty-four paramedic students from two UK ambulance services participated in the focus groups. Usability of the app and its potential were viewed positively. Four major themes were identified: 1) overall opinion of the app for use in paramedic services; 2) incorporating technological applications into the health care setting; 3) improving knowledge and governance; and 4) alternative uses for the app. Subthemes were identified and are presented. Discussion Our results indicate that the pain assessment app constitutes a potentially useful tool in the prehospital setting. By providing access to a tool specifically developed to help identify/assess pain in a user-friendly format, paramedics are likely to have increased knowledge and confidence in assessing pain in patients with dementia.